The threat of currency wars: a European perspective - Zsolt Darvas; Jean Pisani-Ferry (Bruegel, 2010)
In this paper, original written for the Economic and Monetary Affairs Committee (ECON) of the European Parliament on 30 November as part of the series entitled 'The threat of currency wars: global imbalances and their effects on currencies', Bruegel Fellows Jean Pisani-Ferry and Zsolt Darvas argue that the currency war has three manifestations: 1) the inflexible pegs of undervalued currencies; 2) attempts by floating exchange-rate countries to resist currency appreciation; 3) quantitative easing. Europe should primarily be concerned about the first issue, which relates to the renewed debate about the international monetary system.
Keywords: 330; Wechselkurs; Währungspolitik; Wechselkurspolitik; Internationales Währungssystem; EU-Staaten